2019
DOI: 10.7717/peerj.7436
|View full text |Cite
|
Sign up to set email alerts
|

Identification of crucial genes based on expression profiles of hepatocellular carcinomas by bioinformatics analysis

Abstract: Hepatocellular carcinoma (HCC) is one of the most heterogeneous malignant cancers with no effective targets and treatments. However, the molecular pathogenesis of HCC remains largely uncertain. The aims of our study were to find crucial genes involved in HCC through multidimensional methods and revealed potential molecular mechanisms. Here, we reported the gene expression profile GSE121248 findings from 70 HCC and 37 adjacent normal tissues, all of which had chronic hepatitis B virus (HBV) infection, we were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Nevertheless, some research indicated that the effect of ENO3 varies among cancers. ENO3 protein levels were found to be lower in liver cancer tissues than in normal tissues [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some research indicated that the effect of ENO3 varies among cancers. ENO3 protein levels were found to be lower in liver cancer tissues than in normal tissues [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overexpression of ZWINT increased the proliferation of HCC cells by modulating cell cycle-related proteins (58). Using bioinformatics analysis, the hub gene ZWINT was identified and higher expression of ZWINT in HCC predicted poor prognosis in several studies (34,35). The results of our studies also indicated that ZWINT could exert oncogenic effects rather than tumor inhibitory effects on HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters were set as follows: (i) hypergeometric test was used as the selected statistical test; (ii) Benjamini and Hochberg FDR correction was set as selected correction; (iii) selected significance level was 0.05; and (iv) for testing option, we used whole annotation as the reference set. In addition, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis was undertaken using KOBAS (http://kobas.cbi.pku.edu.cn/index.php), which is a webaccessible tool and could identify enriched pathways for an input set of genes by mapping to genes using known In addition, the MCODE plugin (http://apps.cytoscape.org/apps/mcode) in cytoscape software was employed to further identify several PPI submodules using the default parameters of degree cutoff = 2, node score cutoff = 0:2, K-core = 2, and max: depth = 100 [18]. Notably, the PPI score > 3 was considered as the cutoff for screening significantly enriched functional modules from the PPI network.…”
Section: Gene Ontology (Go) and Pathway Enrichment Analysesmentioning
confidence: 99%